The Tsai-Wu failure criterion rationalised in the context of UD composites - Li, Shuguang; Sitnikova, Elena; Liang, Yuning; Kaddour, Abdul-Salam (Elsevier, 2017)
This paper is to rationalise the empirical aspect of the Tsai-Wu failure criterion in the context of UD composites associated with the determination of the interactive strength property F12 based on the analytic geometry. It reveals that the condition of closed failure envelope cannot be satisfied by all UD composites and hence the restriction should be abandoned. Depending on the way the failure envelope opens, UD composites can be classified into two categories. (a) F12 can be determined uniquely using the conventional strength properties with an additional assumption that the material exhibits very high or infinite strength under triaxial compression at a specific stress ratio; or (b) The Tsai-Wu criterion leads to one of the two scenarios: either allowing infinite strength for an in-plane stress state or allowing infinite strength under triaxial stresses involving tension along fibres.